Performance of eco process pozzolann foamed concrete as cement replacement - Nazrin, Sharom (2016)
Nowadays with the demand of construction and advancement of technology, industrial waste becomes potential innovation product for construction materials. Eco Process Pozzolan Foamed Concrete (EPPFC) is the mixing of cement paste with preformed foam which EPP is used as replacement for cement. This study is to investigate the optimum EPP as cement replacement through a series of experimental for five types of mixture of foamed concrete namely FC with 100% of OPC as control sample and 20%, 25%, 30%, 35%, 40% EPPFC. All the specimens have been prepared and tested to determine the compressive strength, workability, porosity and water absorption. From the laboratory test conducted, it can be concluded that the replacement of Eco Process Pozzolan (EPP) that less than 30% will give out a better performance properties compared to control foamed concrete. The replacement of cement with EPP in the concrete mixture leads to the reduce of landfill, with reduction of cement usage there would be less release of carbon dioxide (CO2) into the atmosphere in equivalent proportion. The usage of EPP will also reduce the cost of the project. It is predictable that the foamed concrete with certain percentage of EPP performs better than the control specimens. In future, EPP can be recommended to be used as a new mineral ad mixture for greener construction materials.